FRI0458 EFFICACY AND SAFETY OF PCV13 VACCINATION IN JIA PATIENTS WITH SYSTEMIC MANIFESTATIONS ON TOCILIZUMAB AND CANAKINUMAB TREATMENT. (2nd June 2020) - Vankova, D.; Alexeeva, E.; Dvoryakovskaya, T.; Isaeva, K.; Chomakhidze, A.; Denisova, R.; Mamutova, A.; Fetisova, A.; Gautier, M.; Krekhova, E.; Shingarova, M.; Kriulin, I.; et al.
Abstract : Background: The need for continuous use of immunosuppressive drugs leads to increased risk of developing infectious diseases in children with juvenile idiopathic arthritis with systemic manifestation (sJIA). Questions about choosing the optimal vaccination time and the effect of different classes of therapy on vaccination effectiveness are still open. Objectives: To study clinical and laboratory effectiveness of PCV13-vaccination in children with sJIA on tocilizumab (TOC) and canakinumab (CAN) treatment depending on disease activity stage. Methods: Prospective cohort study included 2 groups of sJIA patients: in stable remission (Remission group, n=53) receiving CAN (n=10) or TOC (n=43) treatment, and in acute stage of disease (Acute group, n=25) which started to received CAN (n=7) or TOC (n=18) either before vaccination (Acute Treated Before subgroup, n=17) or after vaccination (Acute Treated After subgroup, n=8). 0.5 ml of the 13-valent PCV was administered once subcutaneously. Efficacy was evaluated by achieving of protection level of anti-pneumococcal antibodies after 4 weeks and by clinical indicators after 6 month follow-up: frequency of acute respiratory infections, frequency of antibiotics treatment courses, frequency of temporary withdrawal of biologics treatment due to severe infections. Frequency of events were counted per patients-years. Results: Four weeks after vaccination, protection level of anti-pneumococcal antibodies was achieved by for 36 (67.9%) patients in Remission group, 16 (64%) patients in Acute group (intergroup p=0.932), and in 8 (47.06%) patients in Acute Treated Before subgroup and in 8 (100%) patients in Acute Treated After subgroup (intersubgroup p=0.022). PCV13 have shown high clinical effectiveness in both Remission group and Acute group. Reducing of acute respiratory infections frequency was as follows: from 4.57 to 2.15 episodes per patient-year in Remission group (p<0.001) and from 4.32 to 1.28 per patient-year in Acute group (p<0.001). Duration of antibiotics treatment reduced from 2.31 to 0.81 weeks per 1 patient-year in Remission group (p<0.001) from 1.97 to 0.74 in Acute group (p<0.001). Among patients who were previously treated with biologics, frequency of therapy withdrawal reduced from 4.34 to 2.42 per patient-year in Remission group (p<0.001) and from 3.53 to 1.18 in Acute Treated Before subgroup (p=0.002). The incidence of reactions to vaccination of PCV13 (local hyperemia, pain, subfebrile temperature) was similar in groups (22 (41.5%) for Remission group and 7 (28%) for Acute group, p= 0.319). Conclusion: Vaccination with the 13-valent PCV has demonstrated high clinical efficacy and safety in children with sJIA both in the acute stage of the disease and during remission. Vaccination of patients in acute stage of sJIA before treatment has advantages over vaccination during remission or after prolonged immunosuppressive therapy in terms of achieving an adequate vaccine response. Disclosure of Interests: Dariya Vankova: None declared, Ekaterina Alexeeva Grant/research support from: Roche, Pfizer, Centocor, Novartis, Speakers bureau: Roche, Novartis, Pfizer., Tatyana Dvoryakovskaya: None declared, Ksenia Isaeva: None declared, Aleksandra Chomakhidze: None declared, Rina Denisova: None declared, Anna Mamutova: None declared, Anna Fetisova: None declared, Marina Gautier: None declared, Elizaveta Krekhova: None declared, Meyri Shingarova: None declared, Ivan Kriulin: None declared, Anastasiya Kontorovich: None declared, Olga Galkina: None declared, Tatyana Radygina: None declared, Irina Zubkova: None declared, Natalia Tkachenko: None declared, Yanina Orlova: None declared, Mariya Kurdup: None declared, Anna Ismailova: None declared, Alina Alshevskaya: None declared, Andrey Moskalev: None declared, Olga Lomakina: None declared